Pengaruh Pendidikan Agama Kristen dalam Membentuk Etika Profesional pada Mahasiswa Universitas Pattimura - Rahanra, Ivonny Yeany; Tuhumury, Julian (MAN 4 Kota Pekanbaru, 2025)
Students in lectures often prioritize other courses that align with their study programs or interests compared to Christian Religious Education (CRE), which is a mandatory curriculum course. CRE is often perceived as a general subject, causing students not to take it seriously or prioritize it. For many students, Christian Religious Education has already been studied within the family environment, formal education in the church, and formal education at the elementary, junior high, and high school levels. However, Christian Religious Education in higher education serves as a formative pathway aimed at shaping the personality of Christian students as future intellectuals and young professionals. It equips them with a foundation of Christian faith to think, analyze, and plan various aspects of life, as well as to act in ways that build life meaningfully. Recognizing the importance of Christian Religious Education, universities place this course in the early semesters (semester 1 and semester 2) across all faculties at Pattimura University. This study aims to determine the influence of Christian Religious Education in shaping professional ethics among students at Pattimura University, Ambon.